Intramolecular Versus Intermolecular Bonding in Drug Gemcitabine and Nucleobases: A Computational Study - Natarajan Sathiyamoorthy Venkataramanan; Ambigapathy Suvitha; Ryoji Sahara (Molecules)
The adsorption of the drug gemcitabine on nucleobases was investigated using a dispersion-corrected density functional theory (DFT) study. The planar structure of complexes is more stable than those with stacked and buckle-angled configurations. The complexes were found to possess at least two intermolecular hydrogen bonds. The binding energy and interaction energy are both negative, with the highest values observed for the gemcitabine–guanine and the lowest in the gemcitabine–thymine complex. The complex formation was found to be an enthalpy-driven process. Pyrimidine nucleobases have a lower enthalpy of formation than purine nucleobases. The computed HOMA and NICS values on the gemcitabine–nucleobase complexes show a substantial increase compared to the pristine nucleobases. An MESP analysis of the complexes shows a directional interaction and electron density shift between the gemcitabine and the nucleobases. A QTAIM analysis indicates that the intermolecular hydrogen bonds have a partial covalent character. The computed bond energy demonstrates that intermolecular NH⋅⋅⋅N bonds are more potent than other bonds. An energy decomposition analysis using the DLPNO−CCSD(T) method indicates that the complexes exhibit a substantial electrostatic attraction, and dispersion contributes the least towards the system stability. The intermolecular bonds are stronger than the intramolecular bonds in the drug–nucleobase complexes. The strength of intramolecular bonds is determined by the deformation of the gemcitabine ring during the complex formation.